Comparison of nonstructural protein-1 antigen detection by rapid and enzyme-linked immunosorbent assay test and its correlation with polymerase chain reaction for early diagnosis of dengue - Gaikwad, Seema; Sawant, Sandhya S.; Shastri, Jayanthi S. (Journal of Laboratory Physicians, 2017)
INTRODUCTION: Early diagnosis of dengue is important for appropriate clinical management and vector control. Different serological tests based on the principle of immunochromatography and enzyme-linked immunosorbent assay (ELISA) are commonly used for detection of antigen and antibodies of dengue virus. The performance of these tests depends on the sensitivity and specificity. Hence, the study was undertaken to compare nonstructural protein-1 (NS1) antigen detection by rapid and ELISA with real-time polymerase chain reaction (RT-PCR) for diagnosis of dengue.MATERIALS AND METHODS: Prospective laboratory study was carried out on sera samples (n = 200) from clinically suspected cases of dengue. The sera samples were subjected for NS1 antigen detection test by rapid test, NS1 ELISA, and RT-PCR. The results of rapid and ELISA tests were compared with real Time PCR.RESULTS: The sensitivity, specificity, positive, and negative predictive value of rapid dengue NS1 antigen test were 81.5%, 66.7%, 78.2%, and 71.1%, respectively whereas that of NS1 ELISA were 89.9%, 100%, 100%, and 94%, respectively. Concordance of Rapid NS1 and NS1 ELISA with PCR was 75.5% and 94%.DISCUSSION AND CONCLUSION: NS1 antigen ELISA can be implemented in diagnostic laboratories for diagnosis of dengue in the acute phase of illness. The test also has great potential value for use in epidemic situations, as it could facilitate the early screening of patients and limit disease expansion.
Keywords: Dengue; NS1 antigen; polymerase chain reaction; rapid and enzyme-linked immunosorbent assay